Candida albicans keratitis modified by steroid application - Kaoru Araki-Sasaki (Dove Medical Press, 2009)
Kaoru Araki-Sasaki1, Hiroko Sonoyama1, Tsutomu Kawasaki1, Nariyasu Kazama1, Hidenao Ideta1, Yoshitsugu Inoue21Ideta Eye Hospital, Kumamoto City, Kumamoto, Japan; 2Department of Ophthalmology, Tottori University, Koyama-Minami, Tottori, Japan Abstract: The paper reports on Candida albicans ocular infection modified by steroid eye drops. A 74-year-old male complained of conjunctival injection and pain in his right eye three months after pterygium and cataract surgery. After treatment with antibiotics and steroid eye drops for three days, he was referred to our hospital. Clear localized corneal endothelial plaque with injection of ciliary body was observed. No erosion of the corneal epithelium, or infiltration of stromal edema was observed, suggesting that the pathological organism derived from the intracameral region. Because ocular infection was suspected, steroid eye drops were stopped, which led immediately to typical infectious keratitis in the pathological region, with epithelial erosion, fluffy abscess, stromal infiltration, and edema. For diagnostic purposes, the plaque was surgically removed with forceps and the anterior chamber was irrigated with antibiotics. The smear and culture examination from the plaque revealed C. albicans surrounded by neutrophils. However, aqueous fluid and fibrous tissue after gonio procedure contained no mycotic organisms. Topical fluconazole, micafungin, and pimaricin with oral itraconazole (150 mg/day) were effective. Special attention is needed when prescribing steroid eye drops to treat corneal disease especially postoperatively. Diagnosing infectious keratitis is sometimes difficult because of modification by some factors, such as postoperative conditions, scarring, and drug-induced masking. Here, we report on mycotic keratitis modified by postoperative steroid administration. Keywords: Candida albicans, cataract surgery, steroid, mycotic keratitis